Poverty, Growth, and Environment in Brazil : Spatial Insights for Policymaking - World Bank (Washington, DC, 2013)
This report examines the implications of spatial heterogeneity - the uneven distribution of poverty, growth, and environmental assets - for policy. Its goal is to inform a wide set of policies that are either explicitly spatially targeted or may have unanticipated spatial implications. These include poverty alleviation policies targeted on poor municipios; demand-driven poverty alleviation policies; territorial development policies aimed at stimulating growth in a multi-municipio region; growth policies targeted on semi-arid regions; policies to protect environmental assets. The report focuses on clarifying some of the fundamental assumptions and underpinnings of spatially oriented development policies, addressing six questions organized in three sections. Are policies targeted at poor municipios effective in reaching poor people? Do demand-driven policies favor poor people? What explains divergent labor market experiences in rural areas? Are poverty and economic stagnation in the Northeast closely tied to agroclimatic conditions? Is poverty a major determinant of Amazonian deforestation? Is there a steep trade-off between forest protection and agricultural output? The report advances knowledge in each of these areas, but unresolved issues remain for debate and research.